Association of Severity of Lower Extremity Arterial Disease and Overactive Bladder Syndrome: A Cross Sectional Study - Yuksel, Bahar; Ozgor, Faruk; Sahin, Mazlum; Savun, Metin; Sahan, Murat; Caglar, Ufuk; Sarilar, Omer (Urology Journal, 2020)
Purpose: The aim of this study aim is to clarify the relationship between Overactive bladder syndrome (OAB) and severity of lower extremity ischemia by using Fontaine classification system. Materials and Methods: Patients who were diagnosed with lower extremity arterial disease were enrolled into the study. The Fontaine score of each patient was taken and all patients completed the validated Turkish version of OAB-V8 questionnaire. Body mass index, serum creatinine, blood urea nitrogen, cholesterol and fasting plasma glucose levels were measured. The patients were divided into two groups. Patients with OAB-V8 score above 8 were enrolled into group 1 and patients with OAB-V8 score under 8 were enrolled into group 2. Results: At the end of study period, 181 patients who met the inclusion criteria were enrolled into the study. Patients with OAB ? 8 score (n= 79) were compared with patients with OAB < 8 score (n= 102). The mean age and the mean BMI were significantly higher in patients with OAB ? 8 (P = .001 and P = .001, respectively). Also, HDL- cholesterol level was found significantly lower in group 1 patients (P= .001). Multivariate regression analysis showed that presence of Fontaine score ? class 2b, age ? 60 years, BMI ? 30 kg/m2 , and HDL-cholesterol levels < 60 mg/dL were predictive factors for OAB. Conclusion: The present study demonstrated that incidence of OAB is higher in patients with severe lower extremity ischemic symptoms, older age, high BMI, and lower HDL-cholesterol level.